-7 7b + 15 = (-34) 7b = (-34) - 15 7b =(-49) b = (-49) / 7 b= (-7)
2 - 3b = 7b + 12 Let us introduce equal terms (3b - 12 in this specific case) on each side (left and right) of the equal sign, so that the 'b' term is all alone on one side of the equal sign. 2 - 3b + (3 b - 12) = 7b + 12 + (3 b - 12) -10 = 10b b = -1 =============================
7b + 15= -34 First, 7b + 15 - 15 = -34 - 15 So, 7b = -49 Then, 7b/7 = -49/7 And finally, b = -7 So b = -7
68 = 7b - 9 -7b = -68-9 b = (-68-9)/-7 = 11
there is a sign missing -- if 4b +15 = 7b then 3b = 15 and b thus = 5 if 4b - 15 = 7b then 3b = -15 and b = -5
If: 6b+21 = 7b-21 Then: 6b-7b = -21-21 And: -b = -42 So: b = 42
-58
-7 7b + 15 = (-34) 7b = (-34) - 15 7b =(-49) b = (-49) / 7 b= (-7)
2 - 3b = 7b + 12 Let us introduce equal terms (3b - 12 in this specific case) on each side (left and right) of the equal sign, so that the 'b' term is all alone on one side of the equal sign. 2 - 3b + (3 b - 12) = 7b + 12 + (3 b - 12) -10 = 10b b = -1 =============================
7b + 15= -34 First, 7b + 15 - 15 = -34 - 15 So, 7b = -49 Then, 7b/7 = -49/7 And finally, b = -7 So b = -7
6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b
7b divide by 12 will equal 4.2 if b = 7.2
68 = 7b - 9 -7b = -68-9 b = (-68-9)/-7 = 11
there is a sign missing -- if 4b +15 = 7b then 3b = 15 and b thus = 5 if 4b - 15 = 7b then 3b = -15 and b = -5
26 = 3b - 2 - 7b 28 = -4b b = -7
27
7b + 16 = 5b + 247b - 5b = 24 - 162b = 8b = 4